A genetic perspective on leopard (Panthera pardus) conservation units across southern Africa - Thacker, Thomas M (Department of Biological Sciences, 2022)
Conservation units are a tool to guide policy such that conservation goals can be achieved. These units should ideally synthesise a wide array of data – genetic, ecological, demographic – to identify the appropriate scales at which conservation actions can then be directed. Despite being the most widespread of all felids in Africa, and facing numerous threats across its range, it has been proposed that the entirety of southern Africa be considered one conservation unit for leopards (Panthera pardus pardus). This proposal does not take into consideration the likelihood of existing population genetic structure across an increasingly fragmented landscape. Further complicating regional leopard conservation is the variability in conservation policies among the geopolitical leopard-range states. Within this single proposed conservation unit, the patchwork of different legislation does not support a unified policy for leopard conservation. Using a population genetic perspective, this study explores and tests the values and shortcomings of southern Africa as a single conservation unit, and explores the importance of leopard range states within the context of conservation units. Parallel investigations of leopard microsatellite genotype data within the framework of a genetic population study spanning eight countries across southern Africa were carried out. This study presents consilient evidence supporting the finding that southern Africa contains six clusters of unique genetic lineages, and as such does not constitute a single genetic unit. Furthermore, it is shown here that the spatial genetic structure that exists does not correlate with the separate geopolitical range states. Leopard range states within southern Africa instead capture varying levels of unique genetic structure and thus are not of equal value with respect to the conservation of genetic lineages. These findings have several implications for leopard conservation across the region. While the data presented here specifically consider a genetic element of conservation units, they do suggest shortcomings in adopting either the entirety of southern Africa as a single unit or separate geopolitical range states as conservation units. The variability in leopard conservation policy across southern Africa is unlikely to sufficiently protect their existing regional genetic structure. If conservation units are indeed a tool to guide conservation policy, then the southern Africa unit for leopards is potentially less effective than a smaller unit whose spatial scale more accurately captures the discrete variation in population genetic structure. Genetic diversity and population structure is an important component of conservation units and should not be neglected. Currently, however, an appropriate framework allowing for conservation policy to be informed at the necessary scale does not exist; although the establishment of Transfrontier Conservation Areas speaks to the growing acknowledgement that conservation needs to evolve beyond the historical confines of geopolitical range states. The evidence presented here further supports the need for a rethinking of existing policy structures.